Are Australian teachers making the grade? A study of news coverage of NAPLAN testing - Shine, Kathryn (University of Queensland, School of Journalism and Communication, 2015)
The standardised testing of school children has been the subject of significant news media attention in recent years in many developed countries around the world. This article examines the reporting of annual National Assessment Program Literacy and Numeracy (NAPLAN) tests in three major Australian newspapers, with a particular focus on the portrayal of school teachers in the coverage. Overall, teachers were presented as strongly opposed to NAPLAN and the publication of test results, yet the newspapers themselves supported the tests as an important accountability measure. Teachers were depicted as trying to influence the testing system through teaching to the test and cheating. They were presented as generally inadequate as teachers, and were blamed for perceived failings in the educational system. These findings point to implications for teacher recruitment and retention, and for journalism education and training.